2016
DOI: 10.5603/fm.a2015.0125
|View full text |Cite
|
Sign up to set email alerts
|

Selected clinical challenges of a supraclavicular cephalic vein in cardiac implantable electronic device implantation

Abstract: (Folia Morphol 2016; 75, 3: 376-381)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The percentage of each CV type and subtype in all the reported cases is listed in Values represent frequencies and percentages. All the percentages were rounded to the nearest whole number [1,2,3,4,5,6,7,8,9,10,13,14,17,18,19,20,22,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of each CV type and subtype in all the reported cases is listed in Values represent frequencies and percentages. All the percentages were rounded to the nearest whole number [1,2,3,4,5,6,7,8,9,10,13,14,17,18,19,20,22,25].…”
Section: Resultsmentioning
confidence: 99%
“…The unusual courses of the CV beyond the clavicle were found on both sides in some of the cadavers at our university, and one side of the JCV was thicker than the other. However, none of the other papers mentioned this detail, with the exception of Anastasopoulos et al [1,17]. Radiological studies of unusual JCVs focused on one side only, which may explain why the percentage of unusual courses reported on both sides was low.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the clinical importance of the cephalic vein, anatomical variations in its course and diameter of the cephalic vein may limit or complicate insertion of one or several leads. A supraclavicular course of the cephalic vein was reported in 0.2% of cases [ 5 ]. Anastasopoulos et al [ 6 ] reported in 2% of cases the occurrence of anastomosis of cephalic vein with external juguar vein (EJV) via a communicating branch.…”
Section: Introductionmentioning
confidence: 99%
“…At the 22 mm stage of embryonic development the external jugular vein emerges from the plexus and the cephalic vein opens to the external jugular vein via jugulocephalic vein [30]. Passing anterior to the clavicle, the jugulocephalic vein may persist in Prosimia, Anthropoidea: Ceboidea, Cercopithecoidea and in rare cases in humans [9, 21, 30–38].…”
Section: Discussionmentioning
confidence: 99%